Analysis of Sharia Pawn Dispute Resolution in Indonesia in Terms of the Concept of Maqashid Al-Syari'ah - M. Ihsan; Amrizal (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sharia pawn institutions continue to grow marked by the increasing number of financing and customers, so the potential for disputes between rahin and murtahin or with other parties is also increasing. This research aims to analyze the forms of sharia pawn disputes in Indonesia along with the rules and practices of its settlement efforts. This research also intends to analyze the efforts to resolve sharia pawn disputes in Indonesia from the perspective of maqashid al-syari'ah. The research method used is qualitative, with the research subject being PT Pegadaian Syari'ah Unit. The results reveal that the forms of sharia pawn disputes in Indonesia are disputes caused by differences in perception and understanding of the contract, damage/loss of the pawn object, differences in the estimated value of the pawn object, and customer rejection of the auction of the pawned goods. The settlement of the dispute goes through three stages, namely consensus deliberation as the main effort, through the arbitration institution, namely Basyarnas, and the last effort through the Religious Court. The settlement of sharia pawn disputes according to the maqashid al-syari'ah perspective is by basing these efforts on the principle of good faith so as to avoid arbitrary behavior and produce a settlement that brings good to all parties